Womanhood–motherhood: The matrix in times of crisis. (December 2022) - Blanco, Maria-José
This article is a response to the 45th Foulkes lecture given by Dr. Regine Scholz, 'When foundation (Scholz, 2022) matrices move — Challenges for a group analysis of our time'(Scholz, 2022). It looks at women's rights and societies' responses to women as mothers and motherhood as the ultimate crisis. Women's choices, their decisions about being a mother, or not, and their relationship to social and political power is explored, presenting themes connected to motherhood such as abortion, rape, war and displacement as well as climate change.